2010
DOI: 10.3109/09537101003649807
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis associated with enoxaparin: A very rare cause in newborns

Abstract: Newborn infants are most vulnerable to the development of thrombosis because of the developing neonatal hemostatic system, perinatal risk factors and different types of medical conditions. Enoxaparin is the current anticoagulant of choice with advantages for the treatment of neonatal thrombosis. Thrombocytosis induced by enoxaparin has been reported as a rare adverse effect of this medication in adults. However, to our knowledge, in newborns there have been no reported cases to date of thrombocytosis induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…The diagnosis of thrombocytosis induced by drugs is challenging in the presence of other diseases. The cases that developed thrombocytosis due to drugs such as G-CSF, betalactam antibiotics, miconazole, vinca alkaloids, iron therapy, enoxaparin, antipsychotic drugs, adrenaline, glucocorticoids, retinoic acid, ciprofloxacin have been reported [7][8][9][10][11][12]. Mechanisms such as elevation of endogenous IL-6, other cytokines or catecholamines, increased megakaryocytes, increased splenic mobilization, prolonged platelet life-span have been suggested in the etiopathogenesis of ST [9].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of thrombocytosis induced by drugs is challenging in the presence of other diseases. The cases that developed thrombocytosis due to drugs such as G-CSF, betalactam antibiotics, miconazole, vinca alkaloids, iron therapy, enoxaparin, antipsychotic drugs, adrenaline, glucocorticoids, retinoic acid, ciprofloxacin have been reported [7][8][9][10][11][12]. Mechanisms such as elevation of endogenous IL-6, other cytokines or catecholamines, increased megakaryocytes, increased splenic mobilization, prolonged platelet life-span have been suggested in the etiopathogenesis of ST [9].…”
Section: Discussionmentioning
confidence: 99%
“…None of those side effects were observed in our patients. [23][24][25] Moreover, none of the 10 patients treated with r-tPA and LMWH concomitantly had therapy-related hemorrhagic complications. Thus, combined antithrombotic and anticoagulation therapy was used safely in our study group, with a much lower incidence of hemorrhagic complications than reported in many other studies.…”
Section: Discussionmentioning
confidence: 99%
“…15 To improve the application of the data to the Naranjo probability scale, adaptations were made by adding thrombocytosis-specific criteria to improve the grading of case reports for causality, as seen in Table 2. For the purpose of this review, reports of suspected thrombocytosis were systematically assessed for causality (Table 3 16-45 ). The following criteria will be utilized to assess causality of a drug by case report: number of cases described by independent investigators and the Naranjo score associated with causality.…”
Section: Methodsmentioning
confidence: 99%
“…Among the LMWHs, enoxaparin is the most widely used agent. [72][73][74][75] Four cases [28][29][30][31] and 2 case series 29,58 describing thrombocytosis after LMWH administration have been reported. On average, thrombocytosis developed 14 days (range = 3-35 days) after LMWH administration and persisted for 7 days (range = 2-48 days).…”
Section: Low-molecular-weight Heparinsmentioning
confidence: 99%